Editors' Introduction Youth under Control: Punishment and "Reform" in the Neoliberal State - Myers, Randy (Social justice, 2014)
An introduction is presented in which the editors discuss various reports within the journal on topics including the social aspects of youth criminalization and punishment in a neoliberal state, as well as criminal justice reform efforts and various social inequalities.